Shortened breath-hold contrast-enhanced MRI of the liver using a new parallel imaging technique, CAIPIRINHA (controlled aliasing in parallel imaging results in higher acceleration): a comparison with conventional GRAPPA technique. - Ogawa, Masaki; Kawai, Tatsuya; Kan, Hirohito; Kobayashi, Susumu; Akagawa, Yoshihiro; Suzuki, Kazushi; Nojiri, Shunsuke; Ozawa, Yoshiyuki; Shibamoto, Yuta (Abdominal Imaging, 2015)
Purpose: We examined whether the shortened breath-hold 3-dimensional volumetric interpolated breath-hold examination (3D-VIBE) sequence for high acceleration factor (AF) using the controlled aliasing in parallel imaging results in higher acceleration (CAIPIRINHA) could substitute for the conventional sequence using generalized autocalibrating partially parallel acquisition (GRAPPA) in patients undergoing routine gadoxetic acid-enhanced liver MRI.Materials and Methods: Thirty patients with clinically suspected focal liver lesions were scanned using 3D-VIBE sequences with GRAPPA with AF = 2 and AF = 4 and CAIPIRINHA with AF = 4 (acquisition times: 21, 14, and 12 s, respectively) during the hepatobiliary phase. Visual evaluations using a 3- or 5-point scale and signal-to-noise ratio (SNR) analysis were performed for the 3 sequences.Results: For CAIPIRINHA with AF = 4, there was significantly less image noise in both visual evaluation and SNR analysis and fewer parallel imaging artifacts than for GRAPPA with AF = 4 (P < 0.0005); it was equal to GRAPPA with AF = 2 and had fewer motion artifacts than GRAPPA with AF = 2 and 4 (P < 0.0012). The liver edge sharpness and hepatic vessel clarity, lesion conspicuity, and overall image quality were rated significantly higher with CAIPIRINHA with AF = 4 than GRAPPA with AF = 2 and AF = 4 (P < 0.009). For GRAPPA with AF = 4, lesion conspicuity and overall image quality were rated significantly lower than for GRAPPA with AF = 2 (P < 0.012).Conclusion: The shortened breath-hold 3D-VIBE sequence using the new CAIPIRINHA technique with a high AF of 4 was superior to the conventional GRAPPA sequence. The shortened breath-hold sequence using GRAPPA with a high AF of 4 worsened the image quality and lesion conspicuity.